Predator swamping reduces predation risk during nocturnal migration of juvenile salmon in a high‐mortality landscape. (9th May 2016) - Furey, Nathan B.; Hinch, Scott G.; Bass, Arthur L.; Middleton, Collin T.; Minke‐Martin, Vanessa; Lotto, Andrew G.
Summary: Animal migrations are costly and are often characterized by high predation risk for individuals. Three of the most oft‐assumed mechanisms for reducing risk for migrants are swamping predators with high densities, specific timing of migrations and increased body size. Assessing the relative importance of these mechanisms in reducing predation risk particularly for migrants is generally lacking due to the difficulties in tracking the fate of individuals and population‐level characteristics simultaneously. We used acoustic telemetry to track migration behaviour and survival of juvenile sockeye salmon ( Oncorhynchus nerka ) smolts released over a wide range of conspecific outmigration densities in a river associated with poor survival. The landscape was indeed high risk; smolt survival was poor (˜68%) over 13·5 km of river examined even though migration was rapid (generally <48 h). Our results demonstrate that smolts largely employ swamping of predators to reduce predation risk. Increased densities of co‐migrant conspecifics dramatically improved survival of smolts. The strong propensity for nocturnal migration resulted in smolts pausing downstream movements until the next nightfall, greatly increasing relative migration durations for smolts that could not traverse the study area in a single night. Smolt size did not appear to impact predation risk, potentially due to unique characteristics of the system or our inability to tag the entire size range of outmigrants. Movement behaviours were important in traversing this high‐risk landscape and provide rare evidence for swamping to effectively reduce individual predation risk. Abstract : Ecologists have long understood the theoretical advantages of animals migrating in high densities to swamp predators, but empirical evidence is largely lacking. Predation risk of juvenile sockeye salmon smolts migrating downstream in a high‐risk riverine landscape was found to be strongly density dependent. Thus, migration synchronization indeed reduces risk of predation.